2023
DOI: 10.3390/su15032350
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing Engagement with Cultural Heritage through Video Games

Abstract: This paper aims to provide a framework for creating and analyzing cultural heritage games, with the intention of maximizing players’ cognitive, emotional, and behavioral engagement with digital heritage. To achieve this, a set of game design characteristics was identified through semi-structured interviews with experts (n = 16) and subsequently validated through a discussion with university students (n = 19). Grounded theory was then applied to the comments of the experts to create a framework of ten fundament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 64 publications
(84 reference statements)
0
2
0
Order By: Relevance
“…This study analyzed game content by utilizing the 10-attribute cultural heritage engagement framework developed by Camuñas-García et al [15]. To construct this framework, the authors conducted interviews with 16 scholars and designers involved in the creation of cultural heritage games.…”
Section: Content Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…This study analyzed game content by utilizing the 10-attribute cultural heritage engagement framework developed by Camuñas-García et al [15]. To construct this framework, the authors conducted interviews with 16 scholars and designers involved in the creation of cultural heritage games.…”
Section: Content Analysismentioning
confidence: 99%
“…Based on the framework proposed by Camuñas-García et al [15], we identified four significant attributes affecting the cognitive dimension, five impacting the emotional dimension, and three influencing the behavioral dimension (see Table 2).…”
Section: Identitymentioning
confidence: 99%
See 1 more Smart Citation
“…Situated simulation games with situated learning may have the opportunity to enhance learners' reflective process (Hou, 2015), and it can increase students' motivation to learn (Papastergiou, 2009) and promote students' interest in knowledge acquisition (Barab et al, 2009). Designing situated simulation scene spaces for learners to perform tasks or solve puzzles is an effective way to maintain learner interest (Camuñas-García et al, 2023), andJohnson (2002) showed that by interacting with people, objects, or activities in a situated simulation game scene, it provides learners with the opportunity to extend their prior knowledge. In addition, several researchers have applied situated learning with digital games to trigger learners' decision-making experience and guide them to construct their knowledge (Daylamani-Zad et al, 2016;Kelly, 2003;Sung et al, 2015;Vasalou et al, 2017).…”
Section: Theoretical Foundations Of the Gamementioning
confidence: 99%
“…This is why we applied Minecraft, a 3D block-building geogame, for young people to co-design climate adaptation scenarios [16][17][18][19]. Minecraft is categorised as a geogame when there is a 3D representation of a real socio-spatial context, and a design goal for public engagement [20,21].…”
Section: Introductionmentioning
confidence: 99%